Association of Atrial Fibrillation With Cognitive Decline and Dementia Over 20 Years: The ARIC‐NCS (Atherosclerosis Risk in Communities Neurocognitive Study). Issue 6 (7th March 2018) - Chen, Lin Y.; Norby, Faye L.; Gottesman, Rebecca F.; Mosley, Thomas H.; Soliman, Elsayed Z.; Agarwal, Sunil K.; Loehr, Laura R.; Folsom, Aaron R.; Coresh, Josef; Alonso, Alvaro
Abstract : Background: Previous studies have reported that atrial fibrillation (AF) is associated with cognitive decline and dementia. These studies, however, had limited follow‐up, were based mostly on white and highly selected populations, and did not account for attrition. We evaluated the association of incident AF with 20‐year change in cognitive performance (accounting for attrition) and incident dementia in the ARIC (Atherosclerosis Risk in Communities) Study. Methods and Results: We analyzed data from 12 515 participants (mean age, 56.9 [SD, 5.7] years in 1990–1992; 56% women and 24% black) from 1990 to 1992 through 2011 to 2013. Incident AF was ascertained from study ECGs and hospital discharge codes. Cognitive tests were performed in 1990 to 1992, 1996 to 1998, and 2011 to 2013. Incident dementia was clinician adjudicated. We used generalized estimating equations and Cox proportional hazards models to assess the association of time‐dependent AF with change in Z scores of cognitive tests and incident dementia, respectively. During 20 years, 2106 participants developed AF and 1157 participants developed dementia. After accounting for cardiovascular risk factors, including ischemic stroke, the average decline over 20 years in global cognitive Z score was 0.115 (95% confidence interval, 0.014–0.215) greater in participants with AF than in those without AF. Further adjustment for attrition by multiple imputation by chained equations strengthened the association. In addition, incident AF was associated with an increased risk of dementia (hazard ratio, 1.23; 95% confidence interval, 1.04–1.45), after adjusting for cardiovascular risk factors, including ischemic stroke. Conclusions: AF is associated with greater cognitive decline and increased risk of dementia, independent of ischemic stroke. Because cognitive decline is a precursor to dementia, our findings prompt further investigation to identify specific treatments for AF that will delay the trajectory of cognitive decline and, thus, prevent dementia in patients with AF.